Auriculotherapy Modulates Macrophage Polarization to Reduce Inflammatory Response in a Rat Model of Acne - Guang Zuo; Yidan Gao; Guangtong Lu; Ming Bu; Jun Liu; Juncha Zhang; Xisheng Fan; Hao Chen; Xuesong Wang; Yanfen She (Mediators of Inflammation)
Background. The inflammatory response is an important part of the pathogenesis of acne vulgaris. Auriculotherapy has been shown to have a good therapeutic effect on this disease. The aim of this study was to explore the mechanism underlying the anti-inflammatory effect of auriculotherapy in the treatment of acne vulgaris. Methods. Propionibacterium acnes was injected subcutaneously into the ears of rats to establish an animal model of acne. The auriculotherapy intervention in rats consisted of auricular bloodletting therapy (ABT), auricular point sticking (APS), or a combination of both (ABPS). The anti-inflammatory effects of auriculotherapy were evaluated by measuring changes in ear thickness, local body surface microcirculation in the ear, and serum inflammatory factors in rats. The polarization of macrophages was analyzed by flow cytometry, and the expression of TLR2/NF-κB signaling pathway in the target tissues was analyzed using western blot. Results. ABT, APS, and ABPS all reduced the erythema of ear acne, decreased microcirculation in localized ear acne, and decreased serum levels of TNF-α and IL-1β in rats. Meanwhile, the three interventions reduced M1-type macrophages and increased M2-type macrophages; only APS could reduce the expression of TLR2/NF-κB signaling pathway. Conclusion. ABT, APS, and ABPS can improve the inflammatory symptoms of acne and reduce inflammatory cytokines. APS may exert anti-inflammatory effects by altering macrophage polarization and decreasing TLR2/NF-κB expression.